The roots of the cultural deviation of Sufism in the ancient Turkic nomadic culture - Kurmanbek, Akaidar; Osserbayev, Yeldos; Shagyrbay, Almasbek; Azhimov, Bekzhan; Kossalbayev, Bekzhan D. (Frontiers in Communication, 2025)
IntroductionThis study investigates the integration of Sufism into medieval Turkic nomadic culture, analyzing how Sufi rituals, saintly authority, and scholarly networks reshaped social structures and collective identity on the Eurasian steppe.MethodsWe assembled a multidisciplinary corpus, including Divan‑i Ḥikmet verses, 12th-14th‑century hagiographies, waqf endowments, archaeological surveys, and secondary literature, and applied hermeneutic coding in NVivo to identify ritual motifs and symbolic continuities. Ragin’s comparative method organized data across four dimensions: ritual form, institutional patterns, symbolic vocabulary, and succession mechanisms, with intercoder reliability ensured through author reviews.ResultsWe found that communal dhikr ceremonies and whirling dances generated Durkheimian collective effervescence that amplified indigenous circle‑based traditions and accelerated Sufi adoption; that charismatic saints such as Khoja Aḥmad Yasawi transcended tribal loyalties through reputed miracles and moral prestige, founding khanqahs and neutral mazars to facilitate peaceful Islamization; and that Qurʾānic literacy, mastery of Sufi poetry, and formal ijāzas functioned as new forms of cultural capital enabling social mobility. Comparative analysis of South Asian, Anatolian, and North African cases confirms Sufism’s role as a cultural mediator adapting to local cosmologies.DiscussionOur findings show how Sufism simultaneously preserved pre‑Islamic values and transformed Turkic society, revealing the explanatory limits of Durkheim, Weber, and Bourdieu when applied in isolation and highlighting the value of a complementary theoretical approach.